2016
DOI: 10.1155/2016/4940532
|View full text |Cite
|
Sign up to set email alerts
|

Association of RBP4 Genotype with Phenotypic Reproductive Traits of Sows

Abstract: PCR-RFLP was applied to a commercial crossbred pig population in order to investigate the association between polymorphism (SNP) of Retinol-binding protein 4 (RBP4) gene and reproductive performance. 400 sows were genotyped and 2000 records of reproductive traits were used in order to retrieve information about the allele frequencies and the association of the RBP4 gene with main reproductive characteristics of the population. A deviation from the Hardy-Weinberg equilibrium was observed as a result of the AB g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
1
6
1
Order By: Relevance
“…Contrary to our findings, Marantidis et al. (2016) reported that both AA and AB genotypes were favoured in producing higher values of TNB, NBA and number of weaned piglets (NW) traits (piglets/birth), rendering the A allele as an allele with an additive effect. There are many other studies (Messer et al., 1996; Ollivier et al., 1997; Spötter et al., 2009) that reported association of AA genotype with higher TNB, NBA and NW piglets/birth.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our findings, Marantidis et al. (2016) reported that both AA and AB genotypes were favoured in producing higher values of TNB, NBA and number of weaned piglets (NW) traits (piglets/birth), rendering the A allele as an allele with an additive effect. There are many other studies (Messer et al., 1996; Ollivier et al., 1997; Spötter et al., 2009) that reported association of AA genotype with higher TNB, NBA and NW piglets/birth.…”
Section: Resultscontrasting
confidence: 99%
“…A similar pattern of B allele distribution has been reported in Large White and Landrace × Large White populations (Dall’Olio et al., 2010; Marantidis et al., 2016; Rothschild et al., 2000; Wang et al., 2006) and in Black Slavonian sows (Kabalin et al., 2013). Higher allelic values for A allele have been previously reported in Duroc (Drogemuller et al., 2001).…”
Section: Resultssupporting
confidence: 75%
“…Also, Drogemuller et al (2001) were not able to detect significant effects on litter size in a synthetic line for the RBP4 genotypes. Or in contrast, several other studies indicated that the AA genotype has higher TNB and NBA compared to the other genotypes (Rothschild et al, 2000;Omelka et al, 2008, Spotter et al, 2009Marantidis et al, 2015). Rothschild et al (2000) found an additive effect of allele A on TNB and NBA in several commercial lines, but no statistically significant effect of any allele on litter size in the synthetic line.…”
Section: Discussionmentioning
confidence: 90%
“…The roles of RBP4 in reproduction have been supported by accumulating studies. A recent study identified a new single nucleotide polymorphism in RBP4 affecting the production of large litter size of sows [13]. Studies have shown that RBP4 expresses in bovine ovarian cells [14], early vitellogenic oocytes of the trout ovary [15], and ovaries of zebrafish [16].…”
Section: Introductionmentioning
confidence: 99%